The application of multi-baseline digital close-range photogrammetry in three-dimensional imaging and measurement of dental casts. - Xiaoming Fu; Chun Peng; Zan Li; Shan Liu; Minmin Tan; Jinlin Song (PLoS ONE)
Objective To explore a new technique for reconstructing and measuring three-dimensional (3D) models of orthodontic plaster casts using multi-baseline digital close-range photogrammetry (MBDCRP) with a single-lens reflex camera. Study design Thirty sets of orthodontic plaster casts that do not exhibit severe horizontal overlap (>2 mm) between any two teeth were recorded by a single-lens reflex camera with 72 pictures taken in different directions. The 3D models of these casts were reconstructed and measured using the open source software MeshLab. These parameters, including mesio-distal crown diameter, arch width, and arch perimeter, were recorded six times on both the 3D digital models and on plaster casts by two examiners. Statistical analysis was carried out using the Bland-Altman method to measure agreement between the novel method and the traditional calliper method by calculating the differences between mean values. Results The average differences between the measurements of the photogrammetric 3D models and the plaster casts were 0.011-0.402mm. The mean differences between measurements obtained by the photogrammetric 3D models and the dental casts were not significant except for the lower arch perimeter (P>0.05), and all the differences were regarded as clinically acceptable (<0.5 mm). Conclusions Measurements obtained by MBDCRP are compared well with those obtained from plaster casts, indicating that MBDCRP is an alternate way to store and measure dental plaster casts without severe horizontal overlap between any two teeth.